Adolescents’ Nonmedical Use and Excessive Medical Use of Prescription Medications and the Identification of Substance Use Subgroups - Cranford, James A. (2013)
The purpose of this study was to identify subgroups of adolescents based on their past 12-months use of tobacco, alcohol, marijuana, illicit drugs, and nonmedical use and excessive medical use of prescription medications. A cross-sectional web-based survey of adolescents from two middle-and high-school districts in Southeastern Michigan was conducted. The sample included 2,744 middle-school (7(th) and 8(th) grade) and high-school (9(th) through 12(th) grade) students. Participants had a mean age of 14.8 years (SD=1.9); 50.4% were female, 64.1% were Caucasian and 30.6% were African-American. Participants completed measures of past 12-months substance use, parental monitoring, parental substance use, and internalizing and externalizing problems. Exploratory latent class analysis (LCA) indicated four classes. The largest class was comprised of participants with low probabilities of using any substances (Low/No Use class), and the smallest class was comprised of participants with relatively high probabilities of using all substances (Multiple Substances class). A third class included participants with high probabilities of using tobacco, alcohol, and marijuana (TAM). The fourth class consisted of participants with relatively high probabilities of alcohol use, nonmedical prescription drug use, and excessive medical use of prescription drugs (ANM). Female gender predicted membership in the ANM and Multiple Substance classes, and parental monitoring, parental substance use problems, internalizing, and externalizing problems uniquely predicted membership in all three high-risk risk classes. Results indicated three high-risk subgroups of adolescents, each characterized by a different pattern of substance use. Two risk groups are characterized by relatively high probabilities of nonmedical use and excessive medical use of prescription medications.